Marxist Philosophy and Sustainable Economic Development - Ngo, Thanh Quang (Kalágatos, 2025)
This paper explores the relationship between Marxist philosophy and the concept of sustainable economic development, emphasizing how Marxist principles provide a theoretical framework to address economic, social, and environmental challenges in the context of globalization. The analysis focuses on core concepts such as relations of production, class struggle, and surplus value, while linking them to the requirements of sustainable development, including social equity, environmental protection, and economic efficiency. The paper argues that Marxist philosophy not only offers a critical lens to analyze current economic development models but also proposes potential solutions to guide sustainable development in the future. The findings suggest that applying Marxist principles can help restructure economic policies to achieve a balance between economic growth and ecosystem preservation.